Chemical technological decisions of the problem of firm household waste products and their social, ecological and economic aspects. - E. J. Bulychev; L. V. Mironov; S. M. Sukhorukova (Тонкие химические технологии)
The analysis of defects of the ways for burial of solid waiste and tecnologies of incinerations, combustion of solid waiste used in our country is represented. The concept of Universal Biokompleks is offered for the purpose of ecological and есоnomic optimization of these ways.